Tuning the photophysical properties of BODIPY dyes used in DSSCs as predicted by double‐hybrid TD‐DFT: The role of the methyl substituents. Issue 24 (16th August 2022) - Helal, Wissam; Marashdeh, Ali; Alkhatib, Qabas; Qashmar, Hana; Gharaibeh, Mohammed; Afaneh, Akef T.
Abstract: A series of 16 BODIPY dye for DSSC applications are designed with the aim of obtaining a controlled red‐shift of their absorption band maxima. The design is based on changing the number and position of the substituted methyls at the BODIPY moiety. The excited‐state properties of the proposed molecular dyes were predicted with the TD‐B2PLYP/def2‐TZVP level. In going from the fully methyl substituted dye (D1357 ) to the unsubstituted one (D0 ) where all the methyls are replaced by hydrogens, a gradual red‐shift of the lowest and most intense electronic excitation was observed (reaching a max. of 0.8 eV ≈ 220 nm) which resulted from lower HOMO–LUMO gaps and higher conjugation. The tuning function of the methyls on the electronic spectra and other relevant properties of these chemical moieties is carefully analyzed. Replacing the methyls with hydrogens was also found to induce more significant charge‐transfer character, as indicated by natural transition orbital (NTO) and electronic structure analysis, enhanced excited‐state life‐times, and electron transport abilities, while slightly reduce the calculated light harvesting efficiency and the free‐energy of electron injection Δ G inj . Abstract : Double hybrid density functional used to predict the electronic excited state properties of 16 newly proposed BODIPYsensitizer for DSSC applications. Electronic excited state properties are tuned according to the number of methyl groups at the BODIPY moiety. A controlled red‐shift reaching up to 0.8 eV was obtained when replacing all methyls with hydrogens.